The Influence of Perceived Usefulness, Perceived Ease of Use, and Service Quality on Continuance Intention with Satisfaction as an Intervening Variable (Study of Indrive Application Users in Surabaya) - Hafidhuddin, Muhammad Azam; Nurul Azizah (PT Inovasi Pratama Internasional, 2023)
The aim of this research is to analyze the influence of perceived usefulness, perceived ease of use, and service quality on continuance intention with satisfaction as an intervening variable among Indrive application users in Surabaya. This study uses a quantitative approach. The data obtained is primary data obtained through distributing questionnaires to 100 respondents over a period of four weeks. Using the Structural Equation Modeling (SEM) technique with the Partial Least Square (PLS) method approach. The results of this research show that satisfaction is influenced by perceived usefulness, perceived ease of use, and service quality. And continuity intention itself is influenced by perceived ease of use and satisfaction. Meanwhile, perceived usefulness and service quality have no effect on continuance intention.